Exploring the Impact of Social Media on Narcissistic Behavior Among Students in Medan City - Hidayat, Fadhil Pahlevi; Zulfahmi, Zulfahmi; Nasution, Ridwan (Universitas Ahmad Dahlan, 2024)
This study explores the influence of social media on the development of narcissistic behavior among students in Medan City, Indonesia. The research employs a qualitative, descriptive approach to understand how social media platforms like TikTok, Instagram, WhatsApp, and others contribute to both narcissism’s positive and negative aspects. Interviews with respondents reveal a mixed perception of narcissism, with some viewing it as a form of self-appreciation within reasonable limits. In contrast, others see it as an unhealthy phase with negative implications. The study highlights that social media facilitates personality formation and boosts self-confidence but also fosters narcissistic tendencies through excessive self-promotion and attention-seeking behaviors. It concludes that while most respondents do not exhibit severe narcissistic behavior, the potential for harm necessitates mindful social media usage. Recommendations include engaging in meaningful activities, fostering empathy, and providing counseling services to mitigate the adverse effects of narcissism.